Encouraging the practice of self-determined learning in medical education and clinical practice - Saurabh RamBihariLal Shrivastava; Prateek Shrivastava Saurabh (MRIMS Journal of Health Sciences, 2021)
The majority of the freshly joined medical students have limited knowledge of the topics which are being taught and predominantly depend on the knowledge which is passed on to them by the medical teachers. It has been acknowledged that professional doctors have different learning needs in their workplace settings and thus, we have to encourage them for more of self-directed or self-determined learning to ensure that they keep moving forward in their professional career. The term heutagogy refers to a form of self-determined learning, wherein the learner takes the decision about what they wish to learn based on their needs and the approach they wish to adopt for learning the same. In conclusion, heutagogy is the vision for today and tomorrow and all the teachers should facilitate the learning among professionals and medical graduates to improve their proficiency level in the workplace.